Association between elevated C-reactive protein-triglyceride-glucose index and in-hospital major adverse cardiovascular events in acute coronary syndrome patients after percutaneous coronary intervention: a single-center prospective observational study - Fan, Hai; Xia, Dan; Li, Jun; Dong, Xuebin (Frontiers in Endocrinology, 2026)
ObjectiveInflammation and metabolic disorders play important roles in the pathogenesis of acute coronary syndrome(ACS). The C-reactive protein-triglyceride-glucose index(CTI) is a novel combined inflammatory-metabolic indicator. This study aimed to evaluate the association between CTI and in-hospital major adverse cardiovascular events(MACE) in ACS patients after percutaneous coronary intervention(PCI).MethodsThis prospective observational study consecutively enrolled 300 patients who underwent PCI for ACS at our hospital from January 2023 to October 2025. C-reactive protein(CRP),triglyceride(TG), and fasting plasma glucose (FPG) were measured upon admission, and CTI values were calculated. Patients were divided into Q1-Q4 groups according to CTI quartiles. The primary endpoint was in-hospital MACE, defined as a composite of cardiac death, acute stent thrombosis, recurrent myocardial infarction, acute heart failure, and cardiogenic shock. Multivariate logistic regression analysis was used to assess the association between CTI and in-hospital MACE.ResultsAmong the 300 patients, 73 (24. 3%) experienced in-hospital MACE. Compared with the Q1 group, patients in the Q4 group had significantly higher incidence of MACE (10. 7% vs 44. 0%, P<0. 001). Multivariate analysis showed that, after adjusting for traditional risk factors, the highest CTI quartile group(Q4) remained significantly associated with MACE risk (adjusted OR 3. 28, 95%CI 1. 42-7. 56, P , 0. 005). For each standard deviation increase in CTI, the risk of MACE increased by 46% (OR 1. 46, 95%CI 1. 21-1. 76, P<0. 001). CTI demonstrated better predictive value for MACE (AUC, 0. 703, 95%CI 0. 641-0. 766) compared to CRP (AUC, 0. 610), TG (AUC, 0. 655), or FPG (AUC, 0. 678) alone (all P<0. 05). Subgroup analysis showed that CTI had stronger predictive ability in patients with ST-segment elevation myocardial infarction, diabetes, and multivessel disease.ConclusionElevated CTI levels after PCI in ACS patients are significantly associated with increased risk of in-hospital MACE. CTI may be an effective tool for evaluating short-term prognosis in ACS patients after PCI, providing reference for early risk stratification and enhanced monitoring.